2011
DOI: 10.1007/s12013-011-9274-5
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Microcirculation Effect of Local Application of Natural Hirudin on Porcine Random Skin Flap Venous Congestion

Abstract: Medicinal leech therapy is commonly used to treat venous congestion by local application to skin flaps, which are frequently employed in re-construction surgery. In the present study, we investigated the effect of natural hirudin, which was applied locally to treat the venous congestion, in random skin flaps in a Guangxi Bama miniature pig model. The congestive random skin flaps were divided into 3 groups: Group A (control group that was locally applied with saline), Group B (locally applied with 20ATU natural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Ying‐Xin et al reported increased survival in compromised free flaps in rats after subdermal injections of both natural or recombinant hirudin compared to controls injected with saline (Ying‐Xin et al, ). Similarly, increased survival of surface area of compromised random pattern skin flaps after local subdermal injection of natural hirudin compared to controls have been reported in the porcine models (Guo‐Qian et al, ; Zhao et al, ). Furthermore, intravenous injection of recombinant hirudin in regional flaps in rabbits has been reported to increase surface area survival compared with injection of low molecular weight heparin or no injection (Duzgun et al, ).…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…Ying‐Xin et al reported increased survival in compromised free flaps in rats after subdermal injections of both natural or recombinant hirudin compared to controls injected with saline (Ying‐Xin et al, ). Similarly, increased survival of surface area of compromised random pattern skin flaps after local subdermal injection of natural hirudin compared to controls have been reported in the porcine models (Guo‐Qian et al, ; Zhao et al, ). Furthermore, intravenous injection of recombinant hirudin in regional flaps in rabbits has been reported to increase surface area survival compared with injection of low molecular weight heparin or no injection (Duzgun et al, ).…”
Section: Discussionmentioning
confidence: 64%
“…Previous work reports the use of recombinant or natural hirudin in the treatment of venous congestion in animal models (Duzgun et al, ; Guo‐Qian et al, ; Ying‐Xin et al, ; Zhao et al, ). Ying‐Xin et al reported increased survival in compromised free flaps in rats after subdermal injections of both natural or recombinant hirudin compared to controls injected with saline (Ying‐Xin et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…18,19,20 The oxygen content in a fluid (blood) of one deciliter [ C (O 2 )] is expressed by the following equation 19,20 :…”
Section: Discussionmentioning
confidence: 99%